THE MEDIATING ROLE OF AFFECTIVE COMMITMENT ON THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT AND PROCEDURAL JUSTICE ON JOB PERFORMANCE OF CIVIL SERVANT - Heru Kurnianto Tjahjono; Meika Kurnia Puji Rahayu; Awang Dirgantara Putra (Universitas Gadjah Mada, 2020)
This study aims to analyze the mediating role of affective commitment on the effect of perceived organizational support and procedural justice on job performance. Respondents in this study are Civil Servants at the BPS Statistics of the Province and the Special Region of Yogyakarta. The sample used was 188 selected using a purposive sampling technique. Data were analyzed using the Structural Equation Modeling (SEM) method with Analysis Moment of Structural (AMOS) 24.0 software. This study found that perceived organizational support and procedural justice has no significant direct effect on job performance. This research also shows that perceived organizational support and procedural justice have a significant effect on affective commitment, and there is a significant effect between affective commitment on job performance. The finding of this research show that affective commitment was able to mediate perceived organizational support and procedural justice on job performance. Recommendation for leaders, employees, and future research are discussed.